Proses Saponifikasi Minyak Kelapa dan Ekstrak Kulit Pisang untuk Pembuatan Handsoap Antibakteri dan Penyembuhan Luka - Bakhri, Syamsul; Suryanto, Andi; Zainal, Zakinah; Fidya, Nurul (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
This banana peel can be used as a raw material for antiseptic drugs and can also be used as an extract in the manufacture of liquid anti-bacterial soap and wound healing. This study aims to determine the effect of coconut oil and banana peel extract in inhibiting microbial growth, and the effectiveness of hand soap in wound healing. And to determine the effect of coconut oil and banana peel extract on hand soap on organoleptic tests, irritation tests, moisture tests, pH tests and foam tests. This research was started by preparing banana peel extract by maceration method, then coconut oil was heated to a temperature of 70C. KOH solution is added to the coconut oil mixture. After a solid mixture, the soap base is heated by steaming for 3 hours until it becomes clear. After neutral hand soap, citric acid was added to the hand soap, then added banana peel extract formulations with concentrations of (K-) 0, (F1) 100, (F2) 126, (F3) 150 and (F4) 175 grams in each formula. This hand soap has an inhibitory effect on Staphylococcus Epidermidis (SE) bacteria 20 mm which is categorized as very strong, and in terms of wound removal, this liquid soap has the potential to be good at removing wounds. The hand soap produced has a distinctive color and smell, and has a liquid texture. Does not cause irritation to the skin, has a moisturizing effect on the skin, has a pH according to SNI where the set pH range is 8-10, and has foam according to SNI, namely 13-220 mm